Ultraviolet radiation in the Atacama Desert - Cordero, R. R.; Damiani, A.; Jorquera, J.; Sepulveda, E.; Caballero, M.; Fernandez, S.; Feron, S.; Llanillo, P. J.; Carrasco Cerda, Jorge Fernando; Laroze, D.; Labbe, F. (My University, 2018)
The world's highest levels of surface ultraviolet (UV) irradiance have been measured in the Atacama Desert. This area is characterized by its high altitude, prevalent cloudless conditions, and a relatively low total ozone column. In this paper, we provide estimates of the surface UV (monthly UV index at noon and annual doses of UV-B and UV-A) for all sky conditions in the Atacama Desert. We found that the UV index at noon during the austral summer is expected to be greater than 11 in the whole desert. The annual UV-B (UV-A) doses were found to range from about 3.5 kWh/m(2) (130 kWh/m(2)) in coastal areas to 5 kWh/m(2) (160 kWh/m(2)) on the Andean plateau. Our results confirm significant interhemispherical differences. Typical annual UV-B doses in the Atacama Desert are about 40% greater than typical annual UV-B doses in northern Africa. Mostly due to seasonal changes in the ozone, the differences between the Atacama Desert and northern Africa are expected to be about 60% in the case of peak UV-B levels (i.e. the UV-B irradiances at noon close to the summer solstice in each hemisphere). Interhemispherical differences in the UV-A are significantly lower since the effect of the ozone in this part of the spectrum is minor.
Keywords: uv spectroradiometry; uv radiance; atacama